Faktor-Faktor Pemberian Kolostrum Pada Ibu Post Partum Di Puskesmas Kabanjahe Kab. Karo Tahun 2023 - Henny Marlina Situmeang; Kamelia Sinaga; Imran Saputra Surbakti (Lembaga Pengembangan Kinerja Dosen, 2023)
Colostrum is also a thick viscous fluid with a yellowish color that is yellower compared to mature milk. Colostrum is the first fluid secreted by the breast glands, containing tissue debris and residual material found in the alveoli and ducts of the breast glands before and after the puerperium. The IMD approach currently recommended is the breast crawl method (crawling looking for the breast) after the baby The baby is immediately placed in the mother's stomach and left to crawl to find the mother's nipple herself and finally sucks it without help. Many post-natal mothers do not give breast milk or colostrum to their babies. This is due to many factors. One of them is ignorance, making mothers neglect the importance of giving breast milk to babies. Apart from that, most mothers don't understand how colostrum is very beneficial for babies. Research to determine the factors associated with giving colostrum to post partum mothers is very necessary, so that future efforts can be made to ensure that all newborn babies are given colostrum. This study aims to analyze the factors of giving colostrum to post partum mothers at the Kabanjahe District Health Center. Karo. The type of research used in this research is analytical with a cross sectional design. There were 29 research respondents. By collecting secondary and primary data. From the results of statistical tests using Chi-Square, it shows that p = 0.005, which means Ho is accepted (p value < 0.05), so it can be concluded that there is a significant relationship between the knowledge category and colostrum provision. From the results of statistical tests using Chi-Square, it shows that p = 0.005, which means Ho is accepted (p value < 0.05), so it can be concluded that there is a significant relationship between the role categories of health workers in providing colostrum. At the Kabanjahe district health center. Karo in 2023.